A phase 3 definitive RCT of reciprocal reading in high schools in England. (2021) - Cockerill, Maria; Thurston, Allen; O'Keeffe, Joanne; Taylor, Andy
Highlights: Protocol - Phase 3 randomized controlled trial with up to 800 students in 20 high schools. The intervention aims to improve reading comprehension and overall reading. A targeted reading comprehension instruction program delivered by teaching assistants. Abstract: A Phase 3 definitive RCT research design is proposed to determine whether the Reciprocal Reading Secondary program can improve reading outcomes for students aged 11–12. This targeted reading comprehension program is designed to support school staff who will deliver the program to the selected students. The proposed sample will be up to 800 students from 20 schools in England from high socio-economically disadvantaged areas. The program will be delivered to the targeted students over a period of 6 months.